Comparison of mental health between individuals with spinal cord injury and able-bodied controls in Neiva, Colombia (2014)
Although research has investigated the mental health of individuals with spinal cord injury (SCI), an overwhelming majority of this research has been conducted in the United States, Western Europe, and other developed countries. The purpose of this study was to compare the mental health of individuals with SCI with able-bodied controls in Neiva, Colombia, South America. Subjects included 40 Colombians with SCI and 42 age- and sex-matched controls (N = 82). The groups did not differ based on age, sex, years of education, or socioeconomic status. However, controls were twice as likely to be married. Four measures assessed mental health, including satisfaction with life (Satisfaction with Life Scale), depressive symptoms (Patient Health Questionnaire-9), self-esteem (Rosenberg Self-Esteem Scale), andanxiety (State-Trait Anxiety Inventory). In comparison with able-bodied controls, individuals with SCI reported significantly lower mental health on both depressive symptoms and satisfaction with life. These effect sizes were medium and large, respectively. The groups did not differ significantly on measures of self-esteem or anxiety. Mental health of individuals with SCI should be considered a central part of SCI rehabilitation interventions, particularly in Latin America.